The great American western : volume 24 [Volume 24], John Wayne [videorecording (DVD)]. - Wayne, John, 1907-1979; Bradbury, Robert N. (Robert North); Wright, Mack V. (Echo Bridge Entertainment, 2003)
"The trail beyond: Rod Drew is on the hunt for an old family friend's long-lost miner brother and his niece. Drew takes a train to northwestern Canada where he runs into an old buddy, Wabi, on the run after being framed for murder. The pair, hiding from the law, stumbles onto a map leading to the missing Ball family's cabin and a fortune in gold. But soon, not only are the Mounties on their trail, there are some sinister men after Drew's map that will do whatever it takes to their their hands on the gold."--Container.